Study of deuteron elastic scattering on natN by implementing the EBS purposes - Tsintari, P.; Aslanoglou, X.; Axiotis, M.; Kokkoris, M.; Lagoyannis, A.; Misaelides, P.; Ntemou, E.; Patronis, N.; Preketes-Sigalas, K. (HNPS Advances in Nuclear Physics, 2019)
N/A